2021
DOI: 10.1097/prs.0000000000007940
|View full text |Cite
|
Sign up to set email alerts
|

Median Nerve’s Microcirculation in Carpal Tunnel Syndrome: Superb Microvascular Imaging

Abstract: Background: The objectivity of physical and electrodiagnostic tests is limited in detecting carpal tunnel syndrome and its recurrence. Predicting the median nerve blood supply using superb microvascular imaging will allow exact diagnosis and a good follow-up system. The aims of this study include using superb microvascular imaging to correlate with electromyographic diagnosis, and to determine the impact of surgery on improvement in superb microvascular imaging. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 22 publications
2
16
2
Order By: Relevance
“…Compared with CDUS and PDUS, SMI was more accurate in the detection of intraneural blood flow in patients with CTS, yet even in SMI 13 of the 25 healthy subjects showed no visible intraneural vascularisation. Similar results regarding vessel sensitivity in CTS were reported by Karahan et al 9 and Yildiran et al 18 who also reported a correlation between SMI grading and electrophysiology results.…”
Section: Introductionsupporting
confidence: 87%
“…Compared with CDUS and PDUS, SMI was more accurate in the detection of intraneural blood flow in patients with CTS, yet even in SMI 13 of the 25 healthy subjects showed no visible intraneural vascularisation. Similar results regarding vessel sensitivity in CTS were reported by Karahan et al 9 and Yildiran et al 18 who also reported a correlation between SMI grading and electrophysiology results.…”
Section: Introductionsupporting
confidence: 87%
“…We used also SMI in our study to overcome these technical defects. In a literature review, we found four (4) studies investigating intraneural vascularity of median nerve in CTS by SMI [26][27][28][29]. However, the main research focus in Karahan et al [26] and Chen et al [27] was the comparison of SMI and Doppler US.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were observed in our study as well. In a research output of Yildiran et al [29], the vascular indexes were compared before and after open carpal tunnel release in CTS patients. A healthy control group was not considered in this paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SMI may be used to improve the diagnostic accuracy of low-grade digital collateral ligament injuries where there may not be a clear disruption in the ligament substance. Early research on grading of vascularity using SMI in the musculoskeletal system 12,13 has already seen promising results, and with improvements in the technology and conducting similar studies in the hand, it may be possible to stratify and grade injuries to smaller ligaments such as DCL injuries. There are two important limitations to the usage of this technology.…”
Section: Discussionmentioning
confidence: 99%